Role of Energy Community Microgrids in Energy Transition ： A Case Study from a Technological Innovation Systems Perspective - Cui, Li (My University, 2026)
Energy transitions have evolved from linear shifts in dominant energy sources to complex processes requiring fundamental restructuring of socio-technical systems. Contemporary transitions are driven by climate imperatives, efficiency demands, justice concerns, and security risks to achieve sustainability goals. They necessitate coordinated evolution across technological, institutional, and social dimensions. Such coordination is increasingly realized at local and regional levels through new technological and organizational configurations. Energy communities and microgrids have emerged as regional solutions for decentralizing and localizing energy systems. Microgrids integrate distributed energy resources, energy storage systems, and flexible loads within local energy community’s power system capable of both grid-connected and islanded operation. They facilitate renewable energy integration, enhance system flexibility and accessibility, and improve local resilience and efficiency. However, their transformative potential extends beyond technical capabilities. This study examines how energy community microgrids contribute to the energy transition. Employing a qualitative single-case study and functional analysis, the research analyzes an implementation: LEMENE—Lempäälä Energy Community (Finland). The analytical framework draws on the Technological Innovation System approach from innovation policy studies, systematically exploring how microgrids in communities reconfigure local energy systems across technological deployment, institutional embedding, and social participation dimensions. Through functional analysis of system dynamics, this research identifies key drivers, institutional constraints, and challenges shaping microgrid development. Findings reveal that microgrids function not as standalone technical solutions but as socio-technical assemblages whose transformative capacity emerges through interactions with regulatory frameworks, market mechanisms, ownership models, and community engagement patterns. The study contributes theoretically by extending the application of the Technological Innovation System framework by integrating functional analysis with technological, institutional, and social structural dimensions. Empirically, the case study demonstrates that such systems develop through experimentation-driven innovation processes characterized by knowledge development and resource mobilization. At the same time, their broader development and deployment remain constrained by institutional conditions. These findings highlight the importance of policy environments that combine regulatory adaptability, experimental spaces for innovation, and stable long-term policy signals to enable the wider role of energy community microgrids in energy transition processes.
Keywords: innovations; renewable energy sources; microgrids; electrical power networks; energy production (process industry); technology; energy policy; energy systems; energy technology; energy; energy transition; flexibility; decentralisation; fi=Sähkötekniikka|en=Electrical Engineering|; Master’s Programme in Electrical and Energy Engineering